The Effect Of Organizational Culture, Performance Benefits And Transformational Leadership On Employee Performance Mediated By Job Satisfaction: Pengaruh Budaya Organisasi, Tunjangan Kinerja Dan Kepemimpinan Transformasional Terhadap Kinerja Pegawai Yang Dimediasi Oleh Kepuasan Kerja - Evi Kurniawati; Muhtosim Arief; Refren Riadi (OGZ Research & Publishing, 2025)
Abstract This study also examines job satisfaction as a mediating variable in this relationship. Objective : Studi ini menginvestigasi faktor-faktor yang memengaruhi kinerja pegawai di Kantor BKPSDM Bogor, dengan fokus pada peran budaya organisasi, tunjangan kinerja, dan kepemimpinan transformasional. Methods : This study investigates the factors that influence employee performance at the Bogor BKPSDM Office, focusing on the role of organizational culture, performance allowances, and transformational leadership. Research results : The main findings indicate that performance incentives and transformational leadership significantly increase job satisfaction, which in turn positively impacts employee performance. Performance incentives and organizational culture are also shown to directly improve performance. However, organizational culture has no effect on job satisfaction, and transformational leadership does not have a significant direct effect on performance. Furthermore, job satisfaction successfully mediates the effect of performance incentives and transformational leadership on employee performance, highlighting its central role as a link between policies and work outcomes.